Critical Thinking Development Model in Nature Elementary School - Aisha, Sayyidani Issa; Wahdan Najib Habiby (Elementary Teacher Education Program, Majalengka University, 2025)
ABSTRACT This study aims to determine: 1) School programs aimed at developing critical thinking; 2) Preparation of learning aimed at developing critical thinking; 3) Implementation of learning aimed at developing critical thinking; 4) Evaluation of learning aimed at developing critical thinking. This type of research is descriptive-qualitative with a phenomenological approach, with data collection techniques of observation, interviews, and documentation. The sources of this study were three homeroom teachers and PJOK/Outbond teachers. The research location was at SD Muhammadiyah Alam Surya Mentari in Laweyan District, Surakarta. The research time was carried out from October to December 2024. The analysis technique used triangulation data analysis of sources. The study results were as follows: (1) School programs aimed at developing critical thinking, namely through the implementation of the vision and mission of the nature school, annual activities, and extracurricular activities. (2) The preparation of learning needed to develop critical thinking includes the teacher's understanding of critical thinking, learning materials, teaching modules, teaching the school's four pillars, classroom management, learning media, and student conditions. (3) Implementation of learning in developing critical thinking through discussion and HOTS-based questions. (4) Evaluation of learning is carried out using test and non-test methods, namely through observation, such as looking at students' facial expressions and interviews. This can be used as a critical thinking development model in nature schools. Keywords: Students; critical thinking; nature school. ABSTRAK Penelitian ini bertujuan untuk mengetahui: 1) Program sekolah yang bertujuan mengembangkan critical thinking; 2) Persiapan pembelajaran yang bertujuan mengembangkan critical thinking; 3) Pelaksanaan pembelajaran yang bertujuan mengembangkan critical thinking; 4) Evaluasi pembelajaran yang bertujuan mengembangkan critical thinking. Jenis penelitian ini yaitu penelitian deskriptif-kualitatif dengan pendekatan fenomenologi, dengan teknik pengumpulan data observasi, wawancara, dan dokumentasi. Narasumber dari penelitian ini yaitu tiga guru wali kelas dan guru PJOK/Outbond. Tempat penelitian di SD Muhammadiyah Alam Surya Mentari di kecamatan Laweyan, Surakarta. Untuk waktu penelitian dilaksanakan pada bulan oktober sampai desember 2024. Menggunakan teknik analisis data triangulasi sumber. Hasil penelitian yaitu; (1) Program sekolah yang bertujuan mengembangkan critical thinking yaitu melalui pelaksanaan visi-misi sekolah alam, kegiatan tahunan, dan ekstrakulikuler. (2) Persiapan pembelajaran yang diperlukan dalam mengembangkan critical thinking yaitu meliputi pemahaman guru dalam konsep critical thinking, materi pembelajaran, modul ajar, pengajaran 4 pilar sekolah, pengelolaan kelas, media pembelajarandan keadaan peserta didik. (3) Pelaksanaan pembelajaran dalam mengembangkan critical thinking yaitu melalui diskusi dan menggunakan soal berbasis HOTS. (4) Evaluasi pembelajaran dilakukan dengan metode tes dan non tes. Semua itu, dapat dijadikan bentuk model pengembangan critical thinking di sekolah alam. Kata Kunci: Peserta didik; critical thinking; sekolah alam.